Optimization of Adaptive Median Filter and FPGA Implementation - WANG Li-hong; HU Chang-hong; FAN Xian-hong; GAO Chun-ge; ZHANG Xiao-jun; SUN jing-hua (Journal of Harbin University of Science and Technology)
An optimization method of adaptive median filter based on FPGA is proposed to filter the railway image on the problem of adaptive median filter with long time-consuming operation and poor denoising performance at high salt and pepper noise density. The method of pixel noise threshold judgment and secondary median calculation is added to improve the image processing ab山ty under the large salt and pepper noise density. The median value of the peripheral pixels is found in the lru·ge window to reduce iterative processing, which could reduce the complexity and calculation amount of the algorithm. FPGA pipeline structure and parallel processing capab山ties are used to speed up the operation of the algorithm. Compared with the existing median filter with the best simulation filtering effect, the optimization method maintains more complete image de即ls, reduces the amount of calculation by 20% , and increases tl1e peak signal-to-noise ratio by an average of 0. 9 dB. Using FPGA to run optimization algorithms reduces the time consumption to the millisecond level, which provides a basis for the realtime processing of railway image.